2021
DOI: 10.1108/ijlls-03-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Digital technologies, online learning and lesson study

Abstract: PurposeFinding ways in which technology can be used to modify, strengthen, scale up and sustain lesson study (LS) is an emerging field of research. It has become even more important due to a pandemic leading to teacher and student learning being delivered online. The purpose of this paper is to present research findings about experiences of online LS and identify issues for further research.Design/methodology/approachA systematic search of articles from 2010 to 2020 identified 13 relevant papers, and through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In addition, learning study—a combination of Japanese LS and design-based research that is guided by variation theory (Pang & Marton, 2017)—was developed by scholars in Hong Kong and Sweden (Huang & Shimizu, 2016; Pang & Runesson, 2019). Recently, the COVID-19 pandemic has also spurred interest in technology-empowered adaptations of LS (Calleja & Camilleri, 2021; Huang et al, 2023).…”
Section: What Is Lesson Study?mentioning
confidence: 99%
“…In addition, learning study—a combination of Japanese LS and design-based research that is guided by variation theory (Pang & Marton, 2017)—was developed by scholars in Hong Kong and Sweden (Huang & Shimizu, 2016; Pang & Runesson, 2019). Recently, the COVID-19 pandemic has also spurred interest in technology-empowered adaptations of LS (Calleja & Camilleri, 2021; Huang et al, 2023).…”
Section: What Is Lesson Study?mentioning
confidence: 99%
“…Many scholars (e.g., Aykan and Yildirim, 2022) investigated the integration of the Lesson Study Model into distance education during the COVID-19 pandemic, focusing on several dimensions: Lesson Study in distance learning, lesson planning processes, challenges of lesson planning, evaluation, and assessment methods, new strategies, methods, and techniques. Huang et al (2021) in their article, "Digital technologies, online learning and lesson study, " show how various technologies could be used to modify and strengthen lesson study. These studies provide evidence of ways in which technology has been used to support teachers and researchers in carrying out LS in virtual and blended environments.…”
Section: Lesson Studymentioning
confidence: 99%
“…Hence, technology allowed teachers to watch the activities of all the groups to learn what happened when the teacher was not in that group in class and repeatedly watch specific clips that the facilitator annotated with questions. According to Huang et al (2021), conducting online LS effectively to support teachers' learning to teach in such a novel virtual environment is an unprecedented endeavor for educators and researchers.…”
Section: Lesson Studymentioning
confidence: 99%
“…Recently, a variety of online lesson study models have been found to positively impact teaching and learning (Huang et al, 2021a). While the standard lesson study model assumes that teachers prepare and observe instruction in person, the use of digital tools, such as video conferencing and cloud services, can open up new ways of conducting lesson study and supporting teachers' professional development (Hrastinski, 2021;Suh et al, 2021).…”
Section: Research Purposementioning
confidence: 99%
“…Recently, a variety of online lesson study models have been found to positively impact teaching and learning (Huang et al. , 2021a).…”
Section: Introductionmentioning
confidence: 99%